Protection of the author’s moral rights in software development contracts (Revista Direito em Debate, 2022)
The article analyzes software development contracts based on their legal nature and the legal treatment given by Law nº. 9069/1998 (Software Law) to verify the intellectual property right and the moral right of the developer (author) of the program, with the objective of identifying, through the dialectic method based on the analysis of the legislation and relevant judgments, aspects to be observed when carrying out software development  contracts.
Keywords: Software; Moral Rights; Order Agreement; Intellectual property; Development